TRAFFICKING OF ORNAMENTAL FISH IN THE BRAZILIAN AMAZON - Hélio BELTRÃO (Instituto de Pesca, 2021)
The trafficking of ornamental fish is growing on a yearly basis in the Brazilian Amazon. This represents a serious threat to the biodiversity of the region. The objective of this research was to evaluate the trafficking of ornamental fish in the Brazilian Amazon using data from the seizures by the Federal Police and Brazilian Institute of Environment and Renewable Natural Resources - IBAMA. To assess and quantify this illegal trade, we gathered data relating to the period between January 2003 and January 2020. Information was obtained from IBAMA - Amazon - regional superintendence; National Amazon Research Institute - INPA regarding smuggled species that have been recovered and placed in its fish collection. The results show that in 98 seizures made by IBAMA, a total of 170,849 specimens of at least 73 species of 10 families, and 5 orders were recovered. Most of the illegally trafficked species are from the Loricariidae family (31 species, 8.47%). Hypancistrus zebra (Loricariidae), Potamotrygon jabuti, Potamotrygon leopoldi (Potamotrygonidae), Osteoglossum bicirrhosum and Osteoglossum ferreirai (Osteoglossidae) are the most targeted by the traffickers, due to their high value. At least 12 species are undescribed new species and were registered and placed in INPA’s fish collection. The fish followed different routes to reach the border that Brazil, Colombia, and Peru share. We conclude that in order to fight this illegal trade, tougher laws against smugglers, agreements with neighboring countries to combat trafficking, formal environmental education programs for riverine populations, and further scientific studies of smuggled species are necessary.